Pendampingan Santri Baru dalam Beradaptasi di Pondok Pesantren Darullughah Wadda’wah 3, Pasuruan - Sahri; Baharun, Segaf (Al Mu'azarah: Jurnal Pengabdian Kepada Masyarakat, 2023)
This study will explain the assistance of new students in adapting at the Darulluhah Wadda'wah 3 (Tiga) Islamic Boarding School, Pasuruan. This study is important to carry out because the adaptation process really determines the success of students. This study uses techniques. community development by carrying out several series of stages, including: preparation stage, introduction stage, implementation stage, and evaluation stage. This study concludes that assisting new students so that they can adapt better is carried out in three ways, namely motivation, assistance with room activities and the third is lifestyle assistance which is closely related to diet and exercise patterns.